Nanostructuring of GeTiO amorphous films by pulsed laser irradiation - Teodorescu, Valentin Serban; Ghica, Cornel; Maraloiu, Adrian Valentin; Vlaicu, Mihai; Kuncser, Andrei; Ciurea, Magdalena Lidia; Stavarache, Ionel; Lepadatu, Ana M.; Scarisoreanu, Nicu Doinel; Andrei, Andreea; Ion, Valentin; Dinescu, Maria (Beilstein Journal of Nanotechnology, 2015)
Laser pulse processing of surfaces and thin films is a useful tool for amorphous thin films crystallization, surface nanostructuring, phase transformation and modification of physical properties of thin films. Here we show the effects of nanostructuring produced at the surface and under the surface of amorphous GeTiO films through laser pulses using fluences of 10–30 mJ/cm2. The GeTiO films were obtained by RF magnetron sputtering with 50:50 initial atomic ratio of Ge:TiO2. Laser irradiation was performed by using the fourth harmonic (266 nm) of a Nd:YAG laser. The laser-induced nanostructuring results in two effects, the first one is the appearance of a wave-like topography at the film surface, with a periodicity of 200 nm and the second one is the structure modification of a layer under the film surface, at a depth that is related to the absorption length of the laser radiation. The periodicity of the wave-like relief is smaller than the laser wavelength. In the modified layer, the Ge atoms are segregated in spherical amorphous nanoparticles as a result of the fast diffusion of Ge atoms in the amorphous GeTiO matrix. The temperature estimation of the film surface during the laser pulses shows a maximum of about 500 °C, which is much lower than the melting temperature of the GeTiO matrix. GeO gas is formed at laser fluences higher than 20 mJ/cm2 and produces nanovoids in the laser-modified layer at the film surface. A glass transition at low temperatures could happen in the amorphous GeTiO film, which explains the formation of the wave-like topography. The very high Ge diffusivity during the laser pulse action, which is characteristic for liquids, cannot be reached in a viscous matrix. Our experiments show that the diffusivity of atomic and molecular species such as Ge and GeO is very much enhanced in the presence of the laser pulse field. Consequently, the fast diffusion drives the formation of amorphous Ge nanoparticles through the segregation of Ge atoms in the GeTiO matrix. The nanostructuring effects induced by the laser irradiation can be used in functionalizing the surface of the films.
Keywords: fast diffusion; GeTiO film; nanostructuring; pulsed laser annealing; cross-sectional transmission electron microscopy (XTEM)

(untitled) - Stehle, M. (J. Non-Cryst. Solids, 1997)

(untitled) - Van Overschelde, O.; Snyders, R.; Wautelet, M. (Appl. Surf. Sci., 2007)

(untitled) - Sandu, C. S.; Teodorescu, V. S.; Ghica, C.; Canut, B.; Blanchin, M. G.; Roger, J. A.; Brioude, A.; Bret, T.; Hoffman, P.; Garapon, G. (Appl. Surf. Sci., 2003)

(untitled) - Falk, F.; Andrä, G. (J. Cryst. Growth, 2006)

(untitled) - Ganz, D.; Gaparro, G.; Aegerter, M. A. (J. Sol-Gel Sci. Technol., 1998)

(untitled) - Teodorescu, V. S.; Ghica, C.; Sandu, C. S.; Maraloiu, A. V.; Blanchin, M.-G.; Canut, B.; Roger, J. (Dig. J. Nanomater. Biostruct., 2006)

(untitled) - Sheglov, D. V.; Gorokhov, E. B.; Volodin, V. A.; Astankova, K. N.; Latyshev, A. V. (Nanotechnology, 2008)

(untitled) - Perez del Pino, A.; György, E.; Marcus, I. C.; Roqueta, J.; Alonso, M. I. (Nanotechnology, 2011)

(untitled) - Tokarev, V. N.; Khomich, V. Yu.; Shmakov, V. A.; Yamshchikov, V. A. (Dokl. Phys., 2008)

(untitled) - Joya, Y. F.; Liu, Z. (Appl. Phys. A, 2011)

(untitled) - Trice, J.; Thomas, D.; Favazaa, C.; Sureshkumar, R.; Kalyanaraman, R. (Phys. Rev. B, 2007)

(untitled) - Krishma, H.; Favazza, C.; Gangopadhyay, A. K.; Kalyanaraman, R. (JOM, 2008)

(untitled) - Sivakov, V.; Petersen, C.; Daniel, C.; Shen, H.; Mücklich, F.; Mathur, S. (Appl. Surf. Sci., 2005)

(untitled) - Starbova, K.; Mankov, V.; Starbov, N.; Popov, D.; Nihtianova, D.; Kolev, K.; Laude, L. D. (Appl. Surf. Sci., 2001)

(untitled) - Kim, K.; Kim, S.; Lee, S. Y. (Curr. Appl. Phys., 2012)

(untitled) - Marin, D. V.; Volodin, V. A.; Gorotkhov, E. B.; Shcheglov, D. V.; Latyshev, A. V.; Vergnat, M.; Koch, J.; Chichkov, B. N. (Tech. Phys. Lett., 2010)

Laser Processing and Chemistry - Bäuerle, D. (Springer, 2000)

Proceedings Nanotech Conference & Expo - Teodorescu, V. S.; Ghica, C.; Maraloiu, A. V.; Lepadatu, A.-M.; Stavarache, I.; Ciurea, M. L.; Scarisoreanu, N. D.; Andrei, A. (Nanoscale fast Ge diffusion in laser irradiated SiGe thin films, Washington, DC, 12.5.2013-16.5.2013)

(untitled) - Sandu, C. S.; Teodorescu, V. S.; Ghica, C.; Hoffman, P.; Bret, T.; Brioude, A.; Blanchin, M. G.; Roger, J. A.; Canut, B.; Croitoru, M. (J. Sol-Gel Sci. Technol., 2003)

(untitled) - Craciun, V.; Singh, R. K.; Boyd, I. W. (J. Electron. Mater., 2002)

(untitled) - Lim, G.; Kar, A. (Mater. Sci. Eng., B, 2011)

(untitled) - Garcia, B. J.; Martinez, J.; Piqueras, J.; Castaño, J. L.; Muñoz-Yagüe, A. (Appl. Phys. A, 1988)

(untitled) - Stavarache, I.; Lepadatu, A.-M.; Teodorescu, V. S.; Galca, A. C.; Ciurea, M. L. (Appl. Surf. Sci., 2014)

Selective light induced chemical vapour deposition of titanium dioxide thin films - Wagner, E. (École polytechnique fédérale de Lausanne, Switzerland, 2002)

(untitled) - Guosheng, Z.; Fauchet, P. M.; Siegman, A. E. (Phys. Rev. B, 1982)

(untitled) - Sipe, J. E.; Young, J. F.; Preston, J. S.; van Driel, H. M. (Phys. Rev. B, 1983)

(untitled) - Barborica, A.; Mihailescu, I. N.; Teodorescu, V. S. (Phys. Rev. B, 1994)

(untitled) - Tsibidis, G. D.; Barberoglou, M.; Loukakos, P. A.; Stratakis, E.; Fotakis, C. (Phys. Rev. B, 2012)

(untitled) - Tsibidis, G. D.; Stratakis, E.; Aifantis, K. E. (J. Appl. Phys., 2012)

(untitled) - Langer, J. S. (Phys. Rev. E, 2008)

(untitled) - Van Overschelde, O.; Delsate, T.; Snyders, R. (J. Appl. Phys., 2012)

(untitled) - Ojovan, M. I. (Adv. Condens. Matter Phys., 2008)

(untitled) - Richet, P. (Phys. Chem. Miner., 1990)

(untitled) - Pauleau, Y.; Remy, J.-C. (J. Less-Common Met., 1975)

(untitled) - Choi, W. K.; Ho, V.; Ng, V.; Ho, Y.; Ng, S. P.; Chim, W. K. (Appl. Phys. Lett., 2005)